1973
DOI: 10.1128/jb.113.2.825-833.1973
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Isoaccepting Transfer Ribonucleic Acid Species of Bacillus subtilis : Chromatographic Differences Between Transfer Ribonucleic Acids from Spores and Cells in Exponential Growth

Abstract: Differences between the transfer ribonucleic acid (tRNA) of spores and exponentially growing cells of Bacillus subtilis 168 were compared by co-chromatography on reversed-phase column RPC-5. This system gave excellent resolution of isoaccepting species in 1 to 2 hr using a 200-ml gradient. Two methods were used to extract spore tRNAs, a procedure using a Braun homogenizer and a pretreatment with dithiothreitol followed by lysis with lysozyme. Where changes were observed, column elution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…The changes in the profiles of the asporogenous mutant resemble the changes found in the sporeforming strain for tryptophanyl-, leucyl-, and tyrosyl-tRNAs as well as the previously reported changes in threonyl-, glycyl-, seryl-, and arginyl-tRNAs (4). The results verify that these alterations are not artifacts of the method used to extract spores.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The changes in the profiles of the asporogenous mutant resemble the changes found in the sporeforming strain for tryptophanyl-, leucyl-, and tyrosyl-tRNAs as well as the previously reported changes in threonyl-, glycyl-, seryl-, and arginyl-tRNAs (4). The results verify that these alterations are not artifacts of the method used to extract spores.…”
Section: Discussionsupporting
confidence: 85%
“…This paper presents a study of changes in the isoaccepting species of transfer ribonucleic acids (tRNAs) for tyrosine, leucine, lysine, and tryptophan as a function of the stage of development. These amino acid acceptor groups had previously been studied by using tRNAs isolated from cells in exponential growth and from spores, and all four groups had shown differences in chromatographic pattems (4). The present study reveals that the alterations in the isoaccepting tRNAs for tyrosine, leucine, lysine, and tryptophan do not all occur at the same stage of growth and may, therefore, be reflections of different developmental processes.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…BaciZlus subtiZis changes in the percentage of isoaccepting species of tRNAs in different growth stages or in different growth media [1][2][3][4][5][6][7][8][9][10][11]. Several authors have shown that there are two major isoaccepting species of lysine tRNAs in B. subtiZis and that percentage of these species varies in vegetative cells and spores [2,[7][8][9][10][11]. Using lysyl-tRNA-DNA hybridization technique, Chuang et aZ.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) L-Lysine and its immediate precursor, meso-diaminopimelic acid are major constituents of the spore coat and spore cortex (34,37). (iii) The tRNAlYs iso-accepting species undergo both quantitative and qualitative changes at specific times during sporogenesis (18,43,44). Although some asporogenic mutants do not show these changes, others are blocked in these events (19,44).…”
mentioning
confidence: 99%